2014
DOI: 10.1007/s11096-014-9981-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the literature on ‘medication wastage’: an exploration of causative factors and effect of interventions

Abstract: The systematic review has identified a limited literature on medication wastage with a lack of consistency of terms. There is a paucity of robust research focusing on the impact of healthcare interventions on outcomes around medication wastage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 29 publications
0
73
0
4
Order By: Relevance
“…Table 1 describes the panel of experts invited to participate. The two corresponding authors most cited in the systematic review9 were invited by email to participate. The occupant of the highest positions in the Malta Medicines Authority and Department of Health were asked to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 describes the panel of experts invited to participate. The two corresponding authors most cited in the systematic review9 were invited by email to participate. The occupant of the highest positions in the Malta Medicines Authority and Department of Health were asked to participate.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review of the published literature on medication wastage identified a limited evidence base of interventions to reduce wastage and few studies which included wastage as a primary outcome measure 9. Only two studies provided any definition or description of wastage: ‘medicines issued to the patient but not consumed’10 and ‘any drug product, either dispensed by a prescription or purchased over the counter that is never fully consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to address medications wastage issue [3,4,[6][7][8][9][10][11][12][13]. However, the majority of these studies were carried out in outpatient setting [3,4,6,7,[9][10][11]13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of these studies were carried out in outpatient setting [3,4,6,7,[9][10][11]13]. Not much is documented on investigating the causes and cost impact of medications wastage in the inpatient setting [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this include gun, drug and knife amnesties, where individuals can admit to an offence without any risk of reprisal [19][20][21] . In the context of health care, there have also been successful 'DUMP' (Disposal of Unwanted Medication Properly) campaigns, where unwanted medicines have been relinquished to pharmacies for safe disposal without the fear of judgement or retribution 22 . The benefits of these periods of amnesty are that those in need of help may take a unique window of opportunity to seek help, where they may not otherwise have done so.…”
Section: Rationale For Reviewmentioning
confidence: 99%